POLITICAL LEGAL FORMATION OF LEGAL REGULATIONS USING THE CARRY-OVER MECHANISM AND ITS RELATIONSHIP TO GENERAL PRINCIPLES OF GOOD GOVERNMENT - Mohammad Raihan; Qurrata Ayuni; David Aprizon Putra (Universitas Bengkulu, 2024)
Legal politics in the formation of a draft law into law requires a mechanism with a process that is not simple. The process of forming statutory regulations is regulated in Law Number 15 of 2019 concerning the Formation of Legislative Regulations. The planning and preparation stage begins with the National Legislation Program (Prolegnas). In the Prolegnas, it is planned and prepared an agenda for any bills which will be the task of the House of Representatives to be discussed for the next 1 (one) to 5 (five) years and are only valid during the term of office of the DPR in that period. Therefore, a mechanism for